Multifunctional TiO2 overlayer for p-Si/n-CdS heterojunction photocathode with improved efficiency and stability. (November 2018) - Liu, Shanshan; Luo, Zhibin; Li, Lulu; Li, Huimin; Chen, Mengxin; Wang, Tuo; Gong, Jinlong
Abstract: The application of Si-based photocathode for water splitting is largely limited by the low photovoltage and inherent corrosion in aqueous media, where the extraction of photovoltage from Si always requires high temperature doping or complicated deposition techniques. This paper describes a facile solution processed p-Si/n-CdS heterojunction for low cost photovoltage generation from commercially available p-Si substrates, which is further covered by a TiO2 layer. The multifunctional TiO2 layer serves as 1) a passivation layer to fix surface defects of CdS to reduces surface carrier recombination; 2) a hole-blocking layer to reflect photogenerated holes to improve charge separation; 3) a protective layer to avoid the corrosion of CdS and Si substrate. The p-Si/n-CdS/n-TiO2 /Pt photocathode exhibits increased open-circuit voltage (from 49 to 425 mV) and stable H2 production for 1 h. The surface passivation effect and low valence band position of TiO2 both contribute to the improved photovoltage. The solar-to-hydrogen conversion efficiency reaches 2.07%, which is the highest among all Si heterogeneous p-n junction photocathodes in neutral electrolytes. Graphical abstract: fx1 Highlights: High performance. The Si/CdS/TiO2 /Pt photocathode exhibits excellent efficiency in neutral electrolytes. New structure. With TiO2 layer, p-Si/n-CdS p-n heterojunction is applied in PEC for the first time. Low cost. p-Si/n-CdS heterojunction is fabricated by CBD with low cost and simple process. Multifunctional TiO2 layer. The TiO2 layer serves as a passivation layer, hole-blocking layer and protective layer.